Lanie - Kurtz, Jane (American girls collection., 2010)
"Ten-year-old Lanie loves science and nature, but she has a problem: she's an "outside" girl with an "inside" family. She longs get out and go camping, but they all want to stay home. ... But when her favorite aunt comes to stay, Lanie discovers that the wonders of nature are everywhere-even in her own backyard."--Publisher.